An Updated Review of a Novel Drug Delivery System in Medicated Chewing Gum - Kumari, Ch.Surya; Babu, S. Suresh; Begham, Sk. Asha; Venketeswerarao, K.; Durgarao, G. (Asian Journal of Pharmaceutical Research and Development, 2020)
Chewing gums are mobile drug delivery systems. Unlike chewable tablets medicated gums are not supposed to be swallowed and may be removed from the site of application without resort to invasive means and medicated chewing gum MCG is solid, single dose preparation. As for as patient convenience is concerned it is discrete and easy administration without water promotes higher compliance. Since it can be taken anywhere, a chewing gum formulation is an excellent choice for acute medication. The advantages for children and for patients who find swallowing tablets difficult are obvious. The medicated chewing gums are solid, single dose preparations with a base consisting mainly of gums that are intended to be chewed, but not swallowed. They contain one or more active substances, which are released by chewing and are intended to be used for local treatment of mouth diseases or systemic delivery after absorption through the buccal mucosa. This concept is supported by statements that chewing sugar free gum can help reduce the risk of dental caries (cavities). The objective of this systematic study is to appraise existing evidence concerning a possible therapeutic effect of sugar- free chewing gum for patients. MCG represents the newest system with potential uses in pharmaceuticals, over the counter medicines and neutraceuticals.